ENVIRONMENTAL PERFORMANCE EVALUATION - Štrbac, Maja (Economics of Agriculture, 2008)
Environment is surroundings in which an organization operates, including air, water, land, natural resources, flora, fauna, humans, and their interrelation. Environmental objective is overall environmental goal, consistent with the environmental policy, that an organization sets itself to achieve. Environmental Performance Evaluation (EPE) ensures that any business can continually monitor and improve environmental performance.